ANALISIS FAKTOR PENGHAMBAT PEMANFAATAN INTERNET SEBAGAI MEDIA PEMBELAJARAN (Kasus : Mahasiswa Universitas Nusa Cendana) - , Mikael Neno ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Internet is the physical interconnection of computer networks, but in general the Internet is seen as an information resource. For the purposes of education, the Internet is used as a medium of learning that allows the learning process more effective. Through the internet a student will not be relying upon the lecturer. Students can develop their own knowledge or insight to its full potential, using sources of information available on the internet. That is why the world of education, especially higher education in Indonesia, each of which provides internet access to all the academic community. UNDANA as the only public university in East Nusa Tenggara also did not lag behind in providing internet access to all the academic community. Problems that occur are the investment incurred in building the network infrastructure and bandwidth leasing, utilization is not accompanied by efforts to build and empower knowledge-based human resources in order to compete in a global era. The impact is the use of the internet to be low. Because it needs to be identified to determine what factors lead to low utilization of the internet. Identification is done by using an integrated approach between the Technology Acceptance Model and the Theory of Planned Behavior. The data obtained are the primary data using questionnaires to the students as the largest communities in UNDANA especially those in the third semester in science and engineering faculty representing the Natural Sciences and the faculty of social sciences and political science and law faculties representing the Social Sciences. The variables used to identify are the experience, complexity, perceived ease of use, perceived usefulness, subjective norms, situational factors, behavior intention and actual use. Identification results show that the internet has not been fully used for educational purposes by students. Factors that hinder the utilization of internet technology as a medium of learning by students is the experience factor, complexity, perceived usefulness, situational factors and behavior intention.